2005
DOI: 10.1073/pnas.0408928102
|View full text |Cite
|
Sign up to set email alerts
|

Use of targeted glycoproteomics to identify serum glycoproteins that correlate with liver cancer in woodchucks and humans

Abstract: Chronic infection with hepatitis B virus (HBV) is associated with the majority of hepatocellular carcinoma (HCC).The diagnosis of HCC is usually made in the late stages of the disease, when treatment options are limited and prognosis is poor. We therefore have developed a method of glycoproteomic analysis in an attempt to discover serum markers that can assist in the early detection of HBV-induced liver cancer. Briefly, a comparative method for analysis of oligosaccharides released from serum glycoproteins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
327
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(341 citation statements)
references
References 42 publications
13
327
1
Order By: Relevance
“…GP73 was originally described as a resident Golgi type II transmembrane protein expressed primarily in epithelial cells of many human tissues. GP73 antigen expression is barely detectable in healthy subjects, but it is elevated modestly in virus carriers, moderately in patients with cirrhosis, and dramatically in patients with HCC (Block et al, 2005). Mao et al (Mao et al, 2010) compared serum GP73 and AFP levels in 4217 human subjects in a multicenter study in 2010, finding that the sensitivity and specificity of GP73 level for the detection of HCC were 74.6% and 97.4%, respectively, significantly higher than the corresponding values for AFP level.…”
Section: Discussionmentioning
confidence: 99%
“…GP73 was originally described as a resident Golgi type II transmembrane protein expressed primarily in epithelial cells of many human tissues. GP73 antigen expression is barely detectable in healthy subjects, but it is elevated modestly in virus carriers, moderately in patients with cirrhosis, and dramatically in patients with HCC (Block et al, 2005). Mao et al (Mao et al, 2010) compared serum GP73 and AFP levels in 4217 human subjects in a multicenter study in 2010, finding that the sensitivity and specificity of GP73 level for the detection of HCC were 74.6% and 97.4%, respectively, significantly higher than the corresponding values for AFP level.…”
Section: Discussionmentioning
confidence: 99%
“…27 Accordingly, the alteration in protein glycosylation which occurs through varying the heterogeneity of glycosylation sites or changing the glycan structure of proteins on the cell surface and in body fluids has been shown to correlate with the development of numerous disease states, including cancer. 28 Indeed, many clinical biomarkers and therapeutic targets in cancer are glycoproteins 29 such as CA125 in ovarian cancer, Her2/neu in breast cancer, and prostatespecific antigen (PSA) in prostate cancer. PSA is one of the best characterized examples of a secreted glycoprotein used in cancer diagnostics, and its glycoforms have been described.…”
Section: Discussionmentioning
confidence: 99%
“…3 A recent study showed that GOLPH2 was detected in human serum, and it was found to be elevated in the serum and tissue in the woodchuck model of HCC in comparison with the nonneoplastic liver. 4 Thus, GOLPH2 may be a potential marker for the early detection of HCC.…”
Section: Serum Golgi Phosphoprotein 2 Level: a Better Marker Than Alpmentioning
confidence: 99%